Expected Value of Helium Ion Electron Momentum in Momentum Space with Primary Quantum Numbers nâ‰¤3 - Bambang Supriadi; Hana Mardhiana; Wendy Indra Kristiawan; Diana Kamalia; Ike Kumala Sari (Postgraduate, University of Mataram, 2023)
The aim is the expected value of helium ions to determine its properties as a heat transmitter to reactors and chirogenic science. This research is non-experimental research using quantum mechanics literature study methods because there are many previous studies that are relevant to this research. Data on the expected value of electron momentum in helium ions is determined based on numerical calculations using the Matlab 2015a program to simplify calculations using ion expectation calculations in momentum. The results obtained are that the electron momentum value in the helium ion can provide an overview of the average momentum value of the helium ion electrons in momentum space. This research data also shows that in momentum space the expected value of electron momentum decreases as the principal quantum number (n) increases. This can be seen when n=1,l =0 then 3p0 = 1.3146, and when n=3,l =0 then 3p0 = 0.5098.